1997
DOI: 10.1046/j.1365-294x.1997.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of population genetic structure and variability using RAPD markers in the endemic and endangered Limonium dufourii (Plumbaginaceae)

Abstract: Limonium dufourii (Plumbaginaceae) is a triploid species, with apomictic reproduction, endemic to the east mediterranean coast of Spain, where it is present in only six populations with a few individuals in most of them. L. dufourii is included in the Red List of Endangered Species by the IUCN. Genetic variation and population structure in this species has been studied using RAPDs. Twelve different primers provided 124 reliable bands of which 33 were polymorphic among the 165 individuals analysed. Those polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 36 publications
5
51
0
3
Order By: Relevance
“…Sale & al., 1996;Martin & Cruzan, 1999). RAPD phenotypes have been widely used to estimate the genetic structure of populations (Steward & Excoffier, 1996;Palacios & González Candelas, 1997;Jordano & Godoy, 2000;Segarra-Moragues & Catalán, 2003). Despite criticisms raised on the basis of reproducibility (Skroch & Nienhuis, 1995;Jones & al., 1997), a certain re-evaluation for this technique came from a review by Nybom (2004), who indicated that estimates of population genetic structure derived from markers such as RAPD, AFLP and ISSR produce very similar values and may be directly comparable.…”
Section: Introductionmentioning
confidence: 99%
“…Sale & al., 1996;Martin & Cruzan, 1999). RAPD phenotypes have been widely used to estimate the genetic structure of populations (Steward & Excoffier, 1996;Palacios & González Candelas, 1997;Jordano & Godoy, 2000;Segarra-Moragues & Catalán, 2003). Despite criticisms raised on the basis of reproducibility (Skroch & Nienhuis, 1995;Jones & al., 1997), a certain re-evaluation for this technique came from a review by Nybom (2004), who indicated that estimates of population genetic structure derived from markers such as RAPD, AFLP and ISSR produce very similar values and may be directly comparable.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques have been applied to wild species to answer specific questions, mainly regarding the crossing system (Hayward and Hamilton, 1997). Some studies based on microsatellites have been employed in the study of natural populations (Collevatti et al, 2001;Zucchi et al, 2003) but most of the studies are performed with RAPD markers in plants (Chalmers et al, 1992;Wolf andRijn, 1993, Bucci andMenozzi, 1995;Yeh et al, 1995;Maguire and Sedgley 1997;Gillies et al, 1997, Palácios andGonzález-Candelas, 1997;Gallois et al, 1998, Cattan-Toupance et al, 1998, Skabo et al, 1998, and in other organisms (Peever andMilgroom, 1994, Lou et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear DNA markers to measure genetic diversity that do not require a priori knowledge of genome components, such as RAPD and inter-simple sequence repeat (ISSR) markers, have been used to determine genetic variability and population structure of several endemic and endangered plant species (Palacios and González-Candelas 1997;Delgado et al 1999;Rossetto et al 1999;Li and Ge 2001;Lee et al 2003;Torres et al 2003;Bahulikar et al 2004;Chen et al 2004;Segarra-Moragues et al 2005). The applicability of nuclear DNA markers to several species of Juniperus has been demonstrated by previous studies (Adams and Demeke 1993;Adams et al 1998Adams et al , 2003Meloni et al 2006).…”
mentioning
confidence: 99%